The relationship between psychological resilience and depression among the diabetes patients under the background of “dynamic zero COVID-19”: the mediating role of stigma and the moderating role of medication burden - Mei, Yujin; Yang, Xue; Gui, JiaoFeng; Li, YuQing; Zhang, XiaoYun; Wang, Ying; Chen, Wenyue; Chen, Mingjia; Liu, Changjun; Zhang, Lin (Frontiers in Public Health, 2023)
Objective Depression in diabetes patients is caused by their own disease or the surrounding social environment. How to cope with changes in mentality and adjust psychological stress responses, especially under China’s dynamic zero COVID-19 policy, is worth further discussion. The researchers constructed a moderated mediation model to test the effect of psychological resilience during dynamic zero COVID-19 on depression in diabetes patients and the mediating role of stigma and the moderating effect of medication burden. Method From June to September, 2022, data were collected in Jinghu District, Wuhu City, Anhui Province, by multi-stage stratified sampling. Firstly, we selected a tertiary hospital randomly in Jinghu District. Secondly, departments are randomly chosen from the hospital. Finally, we set up survey points in each department and randomly select diabetes patients. In addition, we used the Connor-Davidson Elasticity Scale (CD-RISC) to measure psychological resilience of patients, and used the Stigma Scale for Chronic Illness (SSCI) to measure stigma, medication burden was measured by the Diabetes Treatment Burden Scale (DTBQ), and depression was assessed by the Patient Health Questionnaire-9 (PHQ-9). We used SPSS (version 23.0) and PROCESS (version 4.1) for data analysis. Results (1) Psychological resilience was negatively correlated with stigma, medication burden, and depression. Stigma was positively associated with medication burden and depression. Medication burden and depression are positively correlated, (2) The mediation analysis showed that psychological resilience had a direct predictive effect on depression, and stigma partially mediated the relationship, and (3) Medication burden moderates the direct pathway by which psychological resilience predicts depression; Medication burden moderates the first half of “psychological resilience → stigma → depression.” Conclusion Under the mediating effect of stigma, psychological resilience can improve depression. Medication burden has a moderating effect on the relationship between psychological resilience and depression, and it also has a moderating effect on the relationship between psychological resilience and stigma. These results facilitate the understanding of the relationship mechanisms between psychological resilience and depression.